2013
DOI: 10.1111/wre.12054
|View full text |Cite
|
Sign up to set email alerts
|

An investigation to enhance understanding of the stimulation of weed seedling emergence by soil disturbance

Abstract: Enhanced understanding of soil disturbance effects on weed seedling recruitment will help guide improved management approaches. Field experiments were conducted at 16 site-years at 10 research farms across Europe and North America to (i) quantify superficial soil disturbance (SSD) effects on Chenopodium album emergence and (ii) clarify adaptive emergence behaviour in frequently disturbed environments. Each site-year contained factorial combinations of two seed populations (local and common, with the common pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
7
31
0
1
Order By: Relevance
“…Quantifying genetic and epigenetic contributions to seed dormancy (Chao, Dogramaci, Anderson, Foley, & Horvath, ; Gu, Kianian, & Foley, ) remains an important knowledge gap to be addressed as a means of identifying particularly persistent populations and also to determine whether in‐field environments may be manipulated to reduce weed seed dormancy (Nurse & DiTommaso, ). The efficacy of existing strategies for depleting the soil seedbank through seedling emergence, such as superficial soil disturbance to stimulate seed germination (“stale seedbeds”), may be enhanced by fine‐tuning them to species‐specific dormancy‐breaking requirements through multigenotype, multi‐environment studies (Long et al., ; Schutte & Davis, ; Schutte et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying genetic and epigenetic contributions to seed dormancy (Chao, Dogramaci, Anderson, Foley, & Horvath, ; Gu, Kianian, & Foley, ) remains an important knowledge gap to be addressed as a means of identifying particularly persistent populations and also to determine whether in‐field environments may be manipulated to reduce weed seed dormancy (Nurse & DiTommaso, ). The efficacy of existing strategies for depleting the soil seedbank through seedling emergence, such as superficial soil disturbance to stimulate seed germination (“stale seedbeds”), may be enhanced by fine‐tuning them to species‐specific dormancy‐breaking requirements through multigenotype, multi‐environment studies (Long et al., ; Schutte & Davis, ; Schutte et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Fried et al [2] also reported that, after partitioning out the effects of timing of crop sowing and associated tillage practices, and weather conditions, only 18% of the explained variance in weed composition was due to crop type. Tillage is one of the main drivers of weed community assembly because primary tillage concomitantly buries and stimulates the germination of weed seeds [15], and secondary tillage kills the resulting seedlings, thereby decreasing seed density in the soil [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of a Mediterranean climate, rising temperatures, and altered precipitation patterns also influence the high variability in the occurrence of weed species associated with tillage systems (Cantero‐Martínez et al, ). In this context, combining the farming technique–environment interaction and the subsequently emerged community during a single crop cycle may represent a useful framework for understanding the direct effects of soil tillage systems on the density and diversity of weed communities (Schutte et al, ). Quantitative and qualitative weed data can therefore be used as an indicator regarding the state of the biodiversity in an agro‐ecosystem, and this information can be employed (Albretch, ; Moonen & Bàrberi, ) when selecting management programs (Fried et al, ; Storkey, Moss, & Cussans, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the chosen tillage systems are focused on the depletion of weed seedbanks by the stimulation of weed germination (Riemens, Van der Weide, Bleeker, & Lotz, 2007). Schutte et al (2013) observed differences in seed dormancy loss and germination as a response to superficial soil disturbances. García-Fayos, Bochet, and Cerdá (2010) have described some seed characteristics affecting plant establishment.…”
mentioning
confidence: 99%
See 1 more Smart Citation